Applying Scrumban in Hybrid Software and Hardware Teams: An Experience Report - Meireles, Maria Alcimar Costa; Soares, Karen; Afonso, Ádria; Araújo, Lívia Lobão de; Lobão, Luana; Pinheiro, Gabriel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15079, 2025)
Context:Agile software development methodologies, such as Scrum, Kanban, and Scrumban, have gained prominence in Software Engineering by promoting greater flexibility and workflow visibility. Scrumban, in particular, combines elements of Scrum and Kanban and represents a promising alternative in contexts that demand continuous adaptation, such as hybrid projects integrating software and hardware development. Goal: This study investigates the perception of a multidisciplinary team regarding the application of Scrumban in hybrid projects involving simultaneous software and hardware development. Method: We conducted a survey with 15 team members from a Technological Development Institute to gather perceptions about using Scrumban in a hybrid context. We qualitatively analyzed the responses to identify reported benefits and challenges. Results: The findings suggest that Scrumban significantly enhances the visibility of task progress and fosters alignment among technical teams through visual boards and communication ceremonies. However, participants reported challenges in applying the methodology to hardware development, such as difficulties in task estimation, supplier dependencies, and the rigidity of physical development cycles. They emphasized the need to adapt agile practices to address the specificities of the hybrid context. Conclusion: The experience demonstrated that Scrumban is a valuable approach to promote integration and transparency in hybrid projects, although it requires adjustments to accommodate the particularities of hardware development. This report reinforces the importance of flexible and adaptive methodologies in multidisciplinary environments.